Reproduction and population dynamics of cave-dwelling bats in Costa of Oaxaca, México - Hernández-Aguilar, Itandehui; Santos-Moreno, Antonio (Revista de Biología Tropical, 2020)
Introduction: Reproduction is a critical phase for most living organisms and in bats the reproductive strategies exhibit considerable complexity and variability. Objective: To describe the reproductive patterns and population dynamics of seven bat species (Artibeus toltecus, Carollia perspicillata, Glossophaga soricina, Mormoops megalophylla, Pteronotus fulvus, Pteronotus mesoamericanus and Natalus mexicanus) that roost in one mine (La Mina) and two caves (El Apanguito and Cerro Huatulco) in the State of Oaxaca, in Southeastern México. Methods: Sampling was conducted monthly from July 2016 to June 2017. Bats were captured using a harp trap, which was placed at the entrance of the roosts. The captured bats were identified using taxonomic keys, marked with an aluminum ring, sex and age class were also determined. Reproductive activity was modeled through 63 GLMs for each species (504 in total). The best model was selected according to the Akaike Information Criterion (AIC). Results: A total of 5 836 bats were captured and marked, classified into 14 species, 10 genera, and five families. The most abundant species were: P. fulvus and P. mesoamericanus, representing 41 % and 32.3 % of the captures, respectively. The mormopids M. megalophylla, P. fulvus, P. mesoamericanus, together with N. mexicanus showed a restricted seasonal monoestrous pattern, while the phyllostomids A. toltecus, C. perspicillata, and G. soricina showed a seasonal bimodal polyoestry pattern. The monthly abundance of species fluctuated significantly (H= 13, df= 11, P= 0.044) in the three roosts throughout the entire study period and the best supported GLM that included the seven species showed that the six chosen variables (season, sex, roost, temperature, precipitation and humidity) were positively associated with reproductive activity. Conclusions: The reproductive activity of each species seems to be synchronized with the end of the dry season and the beginning of the rainy season, as well as influenced by factors such as temperature, humidity and roost site.